IMPLICATIONS IN INDONESIAN LANGUAGE LEARNING CLASS VIII SMP N 2 TOROH GROBOGAN - Elyariza Devy Aulia Firdaus; Andayani Andayani; Muhammad Rohmadi (International Journal Labs, 2024)
This study aims to describe and explain the types of implications in learning Indonesian students of Class VIII SMP Negeri 2 Toroh, Grobogan Regency. The research method used is qualitative research with a descriptive approach. The data used in this study is in the form of teacher and student speech in Indonesian learning in which there are implications. The source of data in the study was obtained from speech events in Indonesian learning in grade VIII SMP N 2 Toroh. Techniques used in collecting data using observation, listening, recording, and interview techniques. The results showed that the types of implicatures found in the learning process, namely conventional and unconventional implicatures (conversation) and the results of research that has been done, researchers found some data about the type of implicature of a speech. The data to be analyzed in this study is in the form of speeches of teachers and grade VIII students of SMP N 2 Toroh which contain types of implications